Sustaining Economic Development: A Post Amnesty Therapy on Peace-Building in the Niger Delta - Godwin EGBE; Frederick AHMADU; David IMHONOPI; Ikechukwu ANUKWU (Communications of International Proceedings, 2020)
The Niger Delta is the focal point of attraction in Nigeria because of crude oil, which forms a bulk of the country’s export earnings. In spite of this, the inhabitants are faced with terrible conditions such as; polluted air and water, destruction of aquatic life, land infertility, unemployment, low life expectancy and lack of basic social amenities. These forced the youths into arms struggle. The Federal government instituted amnesty program for militants in the area, in which they were trained, paid stipends and rehabilitated. Unfortunately this was not sustained, as some corrupt politicians hijacked the process for their selfish interest. This paper focused on the challenges of Niger Delta people after the ex-agitators embraced amnesty and the return of crisis in the area. The paper employed the use of primary and secondary data, quantitative research method were used with simple random sampling techniques, 381 copies of questionnaire were administered to respondents in selected Oil producing communities in Rivers State Nigeria. The data obtained from the field were coded and run on SPSS software such that they were presented with the aid of frequency tables and research questions were answered based on this. Findings show that the Niger Delta is not getting better even with the efforts and structures put in place. The recommendations made includes; the need for synergy between transnational companies and host communities, implementation of corporate social responsibilities, increased employment and vocational training for youths, these will reduce social unrest and enhance the standard of living.
Keywords: Pollution; Militants; Oil Companies; Niger Delta